Biology Reduction of Coffee Industry Waste Using Eisenia foetida Earthworms - June Mellawati (Indonesian Chemistry Letter, 2002)
Biology reductions of coffee residue, waste from PT. Torabika industry, Tangerang using earthworm have been carried out. The aim of experiment is to know the ability of earthworm to decompose the waste become verrnicompost and to evaluate it quality. The experiment was used earthworms Eisenia foetida species and 25 - 75 % of cow manure as a medium mixture. The result showed that the structure of vermicomost is soft andblack colors with cation capacity is 17.49 - 21.32 megll00. The mineral content were determined using X-ray Fluorescence Spectrometer (XRF), UV-Vis Spectrophotometer and Kjeldahl, the result showed that the concentrations of N are 0.93 - 0.94 %, CI N 11.26 - 15, K 6.64 - 6.95 %, Ca 12.1 - 17.3 %, P 0.09 - 0.16 %, Mn 0.11 - 0.19 %, Fe 2,01 - 2,69 %, Zn 538 - 779 mgl kg. The earthworm biomass was increased until thirdweeks of vermicomposting.